"Dramat niemiecki", bez tytułu, z czasów Alfonsa II, ks. Ferrary
postaci: Torquato Tasso, Antonio Montecatino, Eleonora d'Este, Alfons II, książę Ferrary
Mf 1842
Keywords: dramat niemiecki 19 w.; literatura niemiecka 19 w.